Functions for Retinoic Acid-Related Orphan Receptor Alpha (RORα) in the Activation of Macrophages During Lipopolysaccharide-Induced Septic Shock - Hams, Emily; Roberts, Joseph; Bermingham, Rachel; Fallon, Padraic G. (Frontiers in Immunology, 2021)
The transcription factor Related Orphan Receptor Alpha (RORα) plays an important role in regulating circadian rhythm, inflammation, metabolism and cellular development. Herein we show that in the absence of functional RORα in mice there is reduced susceptibility to LPS-induced endotoxic shock, with selective decreases in release of pro-inflammatory cytokines. Treatment of mice with a RORα selective synthetic inhibitor also reduced the severity of LPS-induced endotoxemia. The reduction in responses in Rora deficient mice was associated with an alterations in metabolic and pro-inflammatory functions of macrophages, both in vivo peritoneal macrophages and in vitro generated bone marrow derived macrophages. Using LysMCreRorafl/sg mice the reduced susceptibility to LPS was shown to be specific to Rora expression in the macrophages. This study identifies that Rora-mediated regulation of macrophages impacts on the pro-inflammatory responses elicited by LPS.